Efektivitas Kompres Panas Dan Dingin Terhadap Nyeri Neuropati Pada Pasien Kanker Ca Mammae Post Kemoterapi Di Murni Teguh Memorial Hospital - Tambunan, Devita Januarta; Silaen, Harsudianto (Indonesian Trust Nursing Journal, 2024)
Chemotherapy is a treatment process using drugs that aim to destroy or slow down the growth of cancer cells. After chemotherapy, side effects usually occur, such as neuropathic pain. Non-pharmacological ways to reduce pain by doing hot compresses and cold compresses. The objective of this study is to determine the effectiveness of hot and cold compresses on neuropathic pain in breast cancer patients post chemotherapy. This research method is a quasi-experimental study with a two group pre and post test approach without a control group. The research was conducted at Murni Teguh Memorial Hospital Medan. The total population is 60 people, the sample is divided into 2 groups of 30 people each. Sampling technique is purposive sampling. The analysis was performed univariateand bivariate using paired sample t-test with 95% confidence level (=0.05). The result of this study is Neuropathic pain in breast cancer patients post chemotherapy at Murni Teguh Memorial Hospital Medan before being given hot compresses (group 1) in the severe category (60.0%), cold compresses (group 2) experiencing severe pain (63.3%). After being given hot compresses, they experienced mild pain (70.0%), while those who were given cold compresses experienced mild pain (50.0%). There is an effect (difference) of hot and cold compresses on neuropathic pain in breast cancer patients post chemotherapy at Murni Teguh Memorial Hospital Medan, obtained p = 0.033 <0.05. It is concluded that hot compresses are more effective than cold compresses in reducing neuropathic pain after chemotherapy. It is recommended that nurses can provide health education about non-pharmacological measures such as giving hot compresses to breast cancer patients after undergoing chemotherapy to reduce the pain they feel.